Incomplete Cleft Palate in Cornelia de Lange Syndrome - Fortuna, Fory; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Jurnal Plastik Rekonstruksi, 2013)
Background: Cornelia de Lange Syndrome (CdLS) is a rare congenital anomaly inheritance syndrome. The prevalence is 1.6-2.2/100.000 of 8,558,346 births in Europe. Cleft palate is less frequent malformation of this syndrome (21,7%) than other associated malformations. The diagnosis can be obtained clinically based on CdLS diagnostic criteria by USA CdLS Foundation. This is the first case in our hospital. Patient and Method: A case of a 4-year-old girl who came to our attention at Cleft and Craniofacial Center Cipto Mangunkusumo National General Hospital for incomplete cleft palate. Parents’ major concerns was feeding problem. The clinical investigations showed that the child met diagnostic criteria for CdLS as described in literatures. We manage this case in collaboration with paediatric department and other related specialists, including radiologist and craniofacial orthodontist. We performed Veau-Wardill-Kilner’s palataoplasty for the incomplete cleft palate. Paediatric department arranged provision of dietary. Result: This patient with incomplete cleft palate whom we treated by palatoplasty was moderately involved by CdLS (severity score 17). After 3 weeks follow-up, we have overcome feeding problem and body weight gained. Summary: Patient with CdLS needs early multidisciplinary team approach management for maximum outcome, because variety of associated malformations may present and life-threatening. Diagnostic criteria by USA CdLS Foundation assist health care personnel recognize this syndrome early.